PENATALAKSANAAN HOLISTIK PADA PASEN DIABETES MELITUS TIPE 1 TIDAK TERKONTROL PADA REMAJA USIA 17 TAHUN DI PUSKESMAS NATAR MELALUI PENDEKATAN KEDOKTERAN KELUARGA - Aulia Dita Maurizka; Mayasari, Diana (CV. Jasa Sukses Abadi, 2024)
Type 1 diabetes mellitus (DMT1) is a lifelong chronic disorder of glucose homeostasis characterized by autoimmune destruction of insulin-producing pancreatic beta cells, which progressively leads to insulin deficiency and results in hyperglycemia. This disease causes chronic complications that require ongoing treatment management and education for patients and their families. Uncontrolled disease will cause various metabolic complications, macrovascular and microvascular disorders that cause a decrease in the quality and life expectancy of the patient. The purpose of writing this article is to applying the principles of a holistic and comprehensive family doctor approach in detecting internal and external risk factors and solving EBM (Evidence Based Medicine) problems that are family approach and patient centered. This study is a descriptive study of case reports. Primary data were obtained through autoanamnesis and alloanamnesis, physical examination and home visits. Secondary data obtained from the patient's medical record. Patient An.J, aged 17 years, complained of feeling weak and tingling in his legs. The patient has a history of type 1 diabetes on insulin treatment. Patient complaints do not recur and can return to normal activities. Clinically the patient was diagnosed with type 1 diabetes mellitus and diabetic neuropathy. Internal risks are family history of DM, lack of knowledge about type 1 diabetes, high calorie and sugar diet behavior, smoking habits, and alcohol consumption and rarely exercise. External risk with a lack of family knowledge about diabetes mellitus, its triggers and complications faced by the patient. Furthermore, holistic management is carried out, namely non-medical management and mentose medicine with intervention using poster media. In the evaluation, the results obtained in the form of a better understanding of the disease and changes in behavior that have an impact on improving the quality of life. Holistic management with a family medicine approach is needed for patients with type 1 diabetes mellitus with complications of DM neuropathy to identify problems in various aspects in order to support the success of therapy and change patient behavior so as to prevent aggravation of complications.